0719 Does Obstructive Sleep Apnea Affect Development in Children with Down Syndrome?. (12th April 2019) - Sanford, Jillian; Super, Elizabeth; Lam, Derek; Pinter, Joseph
Abstract: Introduction: In typically developing children, obstructive sleep apnea (OSA) is associated with adverse neurocognitive outcomes. Children with Down Syndrome are at increased risk for OSA and have varying degrees of developmental delay, yet minimal data exists on the impact of OSA on the developmental trajectory in children with Down Syndrome. Our objective is to evaluate the relationship between the presence and severity of OSA and developmental outcomes in children with Down syndrome. Methods: Retrospective cohort study of pediatric Down Syndrome patients who have been seen in the Oregon Health and Science University Down Syndrome Clinic between 11/2007 and 1/2015. Retrospective review of polysomnogram (PSG) data (Apnea Hypopnea Index, AHI) and developmental screening data, stratified by age: Peabody Fine Motor Quotient, Gross Motor Function Measure, Rosetti Infant-Toddler Language Scale (ages 0-3yo), Peabody Picture Vocabulary Test (ages 3-6yo), and the Expressive Vocabulary Test (ages 6yo and up). The cohort was stratified by degree of delay on these developmental measures compared to published norms for the general pediatric population. ANOVA was used to compare AHI across categories of developmental delay. The relationship between developmental scores and AHI was assessed using linear and logistic regression for continuous and categorical variables respectively. Exclusion criteria include patients without polysomnogram (PSG) data, developmental screening data, or those without developmental screening data within one year of PSG. Results: Total N = 565. 167 (30%) children underwent PSG, and 60 (11%) underwent PSG within one year of their initial developmental testing. Preliminary analysis did not reveal significant associations with AHI when stratified by age group and degree of developmental delay. Descriptive analysis suggests that there may be an association between AHI and developmental delay in the infant/toddler age group with mild degrees of developmental delay. Further subgroup analysis is in progress. Conclusion: OSA may be associated with negative developmental outcomes in young children with Down syndrome. Evaluation of and treatment for obstructive sleep apnea has the potential to impact developmental trajectory of a vulnerable patient population. Support (If Any): Repository Sharing Agreement (IRB 00010774). OHSU Redcap.